Blood on the snow : the killing of Olof Palme - Bondeson, Jan (Cornell University Press, 2005)
"The Swedish prime minister Olaf Palme, a major figure in world politics and an ardent opponent of apartheid, was shot dead on the streets of Stockholm in February, 1986. At the time of his death, Palme was deeply involved in Middle East diplomacy and was working under UN auspices to end the Iran-Iraq war. Across Scandinavia, Palme's killing had an impact similar to that of the Kennedy assassinations in the United States - and it ignited nearly as many conspiracy theories. Interest in the Palme slaying was most recently stirred by reports of the death of Christer Pettersson, who was tried for the murder twice, convicted the first time, and then acquitted on appeal."